Implementation of Inbound Marketing Strategy through Call to Action by Building an E-Store Website - Febrian, Rizky Tri; Azizah, Azizah -; Purnamasari, Eva -; Sulistiyani, Endang - (Politeknik Negeri Semarang, 2024)
Marketing and product offerings are inextricably linked for a business. Utilizing digital platforms for marketing purposes has a significant effect on how quickly a firm develops. Providing a website that uses inbound marketing as a tool for marketing that is integrated into all social media platforms is the aim of this research. A sales website needs inbound marketing, which focuses on drawing customers with useful and engaging content. Using Call to Action, which serves as an invitation to purchase a product, is one example. The firm Duz Creative Semarang, which produces and sells packages, is the subject of this investigation. WordPress CMS is the development tool of choice for this research, which employs the Waterfall technique. The study's output is a marketing website that is user-friendly, efficient, visually appealing, and educational. Customers may easily discover the services offered on the website, which is linked to all of the business's social media accounts